2015
DOI: 10.1309/ajcpobi5cuzibmo1
|View full text |Cite
|
Sign up to set email alerts
|

VE1 Antibody Is Not Highly Specific for the BRAF V600E Mutation in Thyroid Cytology Categories With the Exception of Malignant Cases

Abstract: VE1 immunocytochemistry in thyroid FNAC as a screening test for BRAF mutations is highly specific for malignant category cases but can be suboptimal due to its high false-positive rate for the nonmalignant cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
0
24
2
2
Order By: Relevance
“…As opposed to immunohistochemical techniques, which have been developed for the detection of the V600E mutation, the present technique is not subjected to the observer interpretation. Equivocal staining has indeed been reported for V600E immunodetection as well as false‐positive and false‐negative results …”
Section: Discussioncontrasting
confidence: 71%
“…As opposed to immunohistochemical techniques, which have been developed for the detection of the V600E mutation, the present technique is not subjected to the observer interpretation. Equivocal staining has indeed been reported for V600E immunodetection as well as false‐positive and false‐negative results …”
Section: Discussioncontrasting
confidence: 71%
“…The antibody appears to be best suited for applications with formalin‐fixed, paraffin‐embedded material such as cell blocks or surgical specimens and for cases diagnosed as PTC. Background and nonspecific staining and a lack of specificity for PTC in the Bethesda indeterminate categories have been reported with liquid‐based preparations or direct smears . In our experience, BRAF IHC does not perform well for routine use with these types of cytologic preparations.…”
Section: Applications Of Braf Mutation Testing In Cytological Specimensmentioning
confidence: 61%
“…Therefore, the commercially available V600E‐specific monoclonal antibody (clone VE1) for IHC is an attractive option for screening for the BRAF V600E mutation in thyroid lesions. Several studies have shown an excellent correlation between strong immunoreactivity for the V600E antibody and the presence of the corresponding mutation, with a sensitivity and specificity of 94% . The antibody appears to be best suited for applications with formalin‐fixed, paraffin‐embedded material such as cell blocks or surgical specimens and for cases diagnosed as PTC.…”
Section: Applications Of Braf Mutation Testing In Cytological Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…[57][58][59] Most of the experience with this antibody comes from studies using aspiration biopsies of thyroid carcinoma and melanoma, in which the antibody appears to work well on both alcohol-and formalin-fixed specimens, as well as in small biopsies and cytology material. [60][61][62] However, to our knowledge, there is no report of IPOX for BRAF in NSCLC cytology specimens.…”
Section: Other Antibodiesmentioning
confidence: 99%